Live sound: tips, techniques, lucky guesses - Slone, Jerry J.
This beginner's guide to the basics of live concert sound mixing and mic techniques is written by industry vet Jerry Slone, whose baptism-by-fire road experiences will teach you need-to-know stuff they simply don't teach in school! It provides easy-to-understand coverage aimed at the novice on topics such as: sound and hearing; microphone models, specs and techniques; mixers; equalization; amplifiers; speakers; the audio chain; schools and universities for continuing education; and much more. Ever since talent show appearances in his pre-teen years, Jerry Slone 's been the guy who got stuck hooking up the PA and trying to tweak it to make it sound better. After graduating from the Recording Industry program at Middle Tennessee State University